Complementary descriptions of Kempnyia gracilenta (Enderlein 1909) and Kempnyia reticulata (Klapálek 1916) (Plecoptera: Perlidae) - Avelino-Capistrano, Fernanda da Silva (Illiesia, 2011)
In this paper the larva of Kempnyia gracilenta (Enderlein) and the larva and female of K. reticulata (Klapálek) from the state of Espírito Santo, Brazil are described and compared to known members of the genus.
Keywords: entomologija; entomology; Plecoptera; vrbnice; stonefly; Brazilija; Perlidae; Kempnyia gracilenta; Kempnyia reticulata; larvae; female; Neotropical; Espírito Santo State; Brazil; larve